The gas morphology of nearby star-forming galaxies - Krieger, Sophia K.; Schinnerer, Eva; Williams, Thomas G.; Querejeta, Miguel; Meidt, Sharon; Emsellem, Éric; Barnes, Ashley; Klessen, Ralf S.; Leroy, Adam K.; Neumann, Justus; Sormani, Mattia C.; Bigiel, Frank; et al. (Astronomy and astrophysics, 2023)
A galaxy’s morphology stems from the secular and environmental processes taking place over the course of its evolutionary history. Thus, it has consistently served as an important tool for gaining insights into galaxy evolution. In this work, we visually classified morphologies on cloud-scales based on the molecular gas distribution of a large sample of 79 nearby main sequence galaxies, using 1″ resolution CO(2-1) ALMA observations taken as part of the PHANGS survey. ...